Ocenka sportivnoj rabotosposobnosti legkoatletov v razlicnye periody trenirovocnogo cikla po aktivnosti summy gljukokortikoidov kory nadpocecnikov - Tambovtseva, R. V.; Nikulina, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 2018)
Objective of the study was to analyze the hormonal control mechanisms behind the total activity of glucocordicoids in the adrenal cortical system in the low- and highly-trained middle-distance racers prior to the precompetitive and competitive periods. Experiments under the study were designed to obtain the following test data: urinal excretion of neutral 17-ketosteroids (17-KS); 17-ketogenous steroids (17-KGS); and free and total 17, 21-dioxi-20- ketosteroids (17-OKS). Urine was tested prior to and 10min after the loads, with the 17-OKS levels tested in the peripheral blood plasma. Venous blood for the tests was sampled prior to, straight after and 3/ 10 minutes after the physical trainings. The study data and analyses showed significant differences in the test data with the growth of the training loads prior to the competitive period. The poorly trained racers were tested with more than 1.5-times growth of the post-training 17-KGS excretion versus the day-off test data. The specific training loads revealed the differences of the low- and highly-trained athletes in the 17-OKS excretion rates that were found to grow in the highly-trained athletes versus the stable levels in the low-trained athletes.